BEHAVIOR OF LEGUMINOUS TREES INOCULATED WITH ARBUSCULAR MYCORRHIZAL FUNGI - Marcos Vinicius Winckler Caldeira; Eliane Maria Ribeiro da Silva; Avílio A. Franco; Magda Lea Bolzan Zanon (Ciência Florestal, 2009)
The effect of the inoculation of arbuscular mycorrhizal fungi on the growth of two legume trees (Cassia leiandra and Chamaecrista desvauxii) was evaluated. The experimental design was completely randomized with four treatments and twenty-five repetitions. The treatments were: Glomus clarum (Nicolson & Schenk), Gigaspora margarita (Becker & Hall), Native Fungi and Control (without inoculation). The seedlings were cultivated in a substratum composed of compost, clay, sand and natural phosphate in the proportion of 6:2:1:1. One Hundred and sixty eight days after seed germination, stem diameter, height, above-ground biomass, below-ground biomass of thick and fine roots, and percent mycorrhizal colonization were evaluated. Although the roots of Chamaecrista desvauxii were colonized with Gigaspora margarita there was no effect of the inoculation on any of the variables measured. Seedlings of Cassia leiandra were colonized by all mycorrhizal fungy, however, there was an increase in the above-ground biomass and below-ground biomass of fine roots only on the seedlings inoculated with Glomus clarum.